Минералы и драгоценные камни - Афонькин Сергей Юрьевич (Узнай мир, 2016)
Экземпляры: ф.10 (20220201) / Инвентарный номер: 61676 / Цена: / Сис.шифр: 26.31 / Авт.знак: С 82 / ГРНТИ: 38.35 / ББК: 26.31я2